2024
DOI: 10.1021/acsami.3c15760
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Piezoelectric/Triboelectric Wearable Nanogenerator Based on Stretchable PVDF–PDMS Composite Films

Qian Chen,
Yuying Cao,
Yan Lu
et al.

Abstract: Hybrid piezoelectric/triboelectric nanogenerators combine the merits of piezoelectric nanogenerators (PENGs) and triboelectric nanogenerators (TENGs), possessing enhanced electrical output and sensitivity. However, the structures of the majority of hybrid nanogenerators are rather complex in integrating both functions, limiting their practical application in wearable electronics. Herein, we propose to construct a piezoelectric/triboelectric hybrid nanogenerator (PT-NG) with a simple structure based on a compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(89 reference statements)
0
0
0
Order By: Relevance
“…Under the influence of this potential, the flow of electrons can be realized to balance the potential. Again, during the recontact of the two layers, the backflow of electrons under the reverse potential can be expected. , Further, the role of the piezoelectric PVDF-HFP layer in enhancing contact electrification was verified upon changing the contacting layer to Al, cellulose paper, nitrile, or Teflon (poly­(tetrafluoroethylene)PTFE). As shown in Figure (d), when different counter layers are in contact with ZnO nanorods, diverse outputs can be obtained depending upon the tendency of the layer to attract electrons.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Under the influence of this potential, the flow of electrons can be realized to balance the potential. Again, during the recontact of the two layers, the backflow of electrons under the reverse potential can be expected. , Further, the role of the piezoelectric PVDF-HFP layer in enhancing contact electrification was verified upon changing the contacting layer to Al, cellulose paper, nitrile, or Teflon (poly­(tetrafluoroethylene)PTFE). As shown in Figure (d), when different counter layers are in contact with ZnO nanorods, diverse outputs can be obtained depending upon the tendency of the layer to attract electrons.…”
Section: Resultsmentioning
confidence: 94%
“…For example, Zhang et al reported the development of a flexible self-powered UV photodetector by coupling the triboelectric and photoelectric effects in a ZnO nanowire-based system showing a responsivity of 1.4 mA/W . Chen et al demonstrated a polyvinylidene fluoride (PVDF)–polydimethylsiloxane (PDMS)-based hybrid nanogenerator for the detection of finger movement, gesture recognition, and monitoring respiration …”
Section: Introductionmentioning
confidence: 99%
“…Energy harvesting and conversion devices using nanotechnology have received increasing attention recently as they may play a crucial role in building and driving self-powered nanodevices and nanosystems. Nanogenerators are devices that convert thermal and chemical energy into electrical energy, effectively collecting energy from various low-frequency mechanical movements from the environment. Self-powered sensors based on nanogenerators can be used as data acquisition units for traffic, human movement, meteorological environment, and gas sensors. In recent years, it has been reported that many wind-driven energy harvesters can be used to capture energy from the surrounding flow field to power sensing nodes or wireless sensing systems for continuous monitoring. Self-powered sensors are an important application development direction of nanogenerators. The development of fully self-powered systems that do not rely on traditional energy systems such as mains or batteries is of great value to the future design of the IoT. …”
Section: Introductionmentioning
confidence: 99%